Radiation–Induced Signaling Results in Mitochondrial Impairment in Mouse Heart at 4 Weeks after Exposure to X-Rays - Barjaktarovic, Zarko; Schmaltz, Dominik; Shyla, Alena; Azimzadeh, Omid; Schulz, Sabine; Haagen, Julia; Dörr, Wolfgang; Sarioglu, Hakan; Schäfer, Alexander; Atkinson, Michael J.; Zischka, Hans; Tapio, Soile (PLOS ONE, 2011)
Backround Radiation therapy treatment of breast cancer, Hodgkin's disease or childhood cancers expose the heart to high local radiation doses, causing an increased risk of cardiovascular disease in the survivors decades after the treatment. The mechanisms that underlie the radiation damage remain poorly understood so far. Previous data show that impairment of mitochondrial oxidative metabolism is directly linked to the development of cardiovascular disease. Methodology/Principal findings In this study, the radiation-induced in vivo effects on cardiac mitochondrial proteome and function were investigated. C57BL/6N mice were exposed to local irradiation of the heart with doses of 0.2 Gy or 2 Gy (X-ray, 200 kV) at the age of eight weeks, the control mice were sham-irradiated. After four weeks the cardiac mitochondria were isolated and tested for proteomic and functional alterations. Two complementary proteomics approaches using both peptide and protein quantification strategies showed radiation-induced deregulation of 25 proteins in total. Three main biological categories were affected: the oxidative phophorylation, the pyruvate metabolism, and the cytoskeletal structure. The mitochondria exposed to high-dose irradiation showed functional impairment reflected as partial deactivation of Complex I (32%) and Complex III (11%), decreased succinate-driven respiratory capacity (13%), increased level of reactive oxygen species and enhanced oxidation of mitochondrial proteins. The changes in the pyruvate metabolism and structural proteins were seen with both low and high radiation doses. Conclusion/Significance This is the first study showing the biological alterations in the murine heart mitochondria several weeks after the exposure to low- and high-dose of ionizing radiation. Our results show that doses, equivalent to a single dose in radiotherapy, cause long-lasting changes in mitochondrial oxidative metabolism and mitochondria-associated cytoskeleton. This prompts us to propose that these first pathological changes lead to an increased risk of cardiovascular disease after radiation exposure.